Factores adversos al fomento de hábitos de estudio y aprendizaje en educación superior: Un estudio de caso - Climént Bonilla, Juan Bautista (Universidad de Costa Rica, 2018)
Achievement of academic and professional competences requires the systematization and developmental balance among physical and cognitive skills and suitable habits and routines of study and learning. The research, on which this article is based, consists of a case study whose main problem is the lack of good habits and routines of study and learning for the academic progress of a group of 31 students throughout a module (course) of the Veterinary Medicine Career, which is taught at the Universidad Autónoma Metropolitana, campus Xochimilco (UAM-Xochimilco), in Mexico City. The main purpose of this research is the identification and analysis of adverse factors hindering the promotion of good study and learning habits in the context of the case study. The characteristics of the observed situation are analyzed from different approaches of interest within the framework of qualitative research. The identification of six adverse factors is highlighted: three of them as habits and routines that compete with the desired study and learning habits; and three more, as a result of the circumstances, contingencies, and unforeseen difficulties that complicate or hinder students' academic achievement, especially in aspects concerning the procedural learning of physical and cognitive skills. The reported findings emphasize the importance of observing higher education challenges from a broad perspective of contexts.